INFLUENCE OF CLARITY OF BUDGET TARGET TOWARDS MANAGERIAL PERFORMANCE OF SATUAN KERJA PERANGKAT KOTA (SKPK) OF KOTA BANDA ACEH - Miranda, M; Aliamin, A (Muhammadiyah International Journal of Economics and Business, 2018)
This study aims to determine the effect of clarity of budget targets with managerial performanceof City Government Work Unit (Satuan Kerja Perangkat Kota/SKPK) of Banda Aceh. The samplein the study amounts to 90 people from the total population. The data are collected by usingquestionnaires; and they are analyzed qualitatively and quantitatively. Data analysis is conductedto see the impact of dependent variable towards the independent variable using simple regressionequation analysis using SPSS V 22 program. The results of research show positive linear relationand correlation between clarity of budget target and managerial performance. Furthermore, thereis positive and significant influence of clarity of budget target variable on managerial performanceof City Government Work Unit of Banda Aceh. Lastly, this study aims to determine the effect ofaccounting information system of the quality of financial statements of the Office of FinancialManagement Agency of Banda Aceh.